2022
DOI: 10.3390/cells11030370
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1 Regulates Porcine Spermatogonial Adhesion and Proliferation through Modulating MMP3/10 Transcription

Abstract: The transition from gonocytes into spermatogonia takes place during the homing process. A subpopulation of undifferentiated spermatogonia in niche then shifts to spermatogonial stem cells (SSCs), accompanied by the self-renewal ability to maintain life-long fertility in males. Enormous changes in cell morphology, gene expression, and epigenetic features have been reported during spermatogenesis. However, little is known about the difference of these features in SSCs during aging. Here, we examined the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Setdb1, also termed ESET, is a histone methyltransferase and it participates in silencing genes through H3K9 trimethylation in the promoter region [ 9 ]. Setdb1 is involved in many pathological and physiological processes, such as carcinogenesis [ 10 , 11 ], cell lineage differentiation during embryogenesis [ 12 ], X chromosome inactivation [ 13 ], and transcriptional regulation [ 14 , 15 ]. Importantly, several studies have reported that Setdb1 plays a crucial role in bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Setdb1, also termed ESET, is a histone methyltransferase and it participates in silencing genes through H3K9 trimethylation in the promoter region [ 9 ]. Setdb1 is involved in many pathological and physiological processes, such as carcinogenesis [ 10 , 11 ], cell lineage differentiation during embryogenesis [ 12 ], X chromosome inactivation [ 13 ], and transcriptional regulation [ 14 , 15 ]. Importantly, several studies have reported that Setdb1 plays a crucial role in bone formation.…”
Section: Introductionmentioning
confidence: 99%